Sedimentological storm and tsunami record of Loch Flugarth, Shetland Islands (UK) - Heß, Katharina; Engel, Max; Koutsodendris, Andreas (Universität, 2023)
Severe storm surges pose a major hazard to the coasts of northwestern Europe. Therefore, high-resolution records of past North Atlantic storminess ...